PENINGKATAN LITERASI DAN KEAMANAN DIGITAL DI DESA SANGGARIA KEEROM-PAPUA - Musfiroh; Sanmas, Masni; Nahria; Sungga Dirgantari, Annisagita; Nur Jaya, Muhammad; Laili, Izzatul (Education and Talent Development Center of Indonesia, 2025)
The rapid advancement of Information and Communication Technology (ICT) has significantly shaped modern society. However, this widespread technological presence is not matched by an equal rise in digital literacy and cybersecurity awareness, particularly in Indonesia's frontier, outermost, and underdeveloped regions (3T areas) such as Sanggaria Village in Keerom Regency, Papua. The primary goal of this community service initiative is to increase digital literacy and cybersecurity awareness among the local population, especially the youth, who are among the most active users of digital technology. A lack of cybersecurity knowledge makes the community vulnerable to various forms of cybercrime. Therefore, this program focuses on educating residents especially teenagers about the importance of digital safety and responsible technology use. The target audience includes the general public, with a specific emphasis on youth, given their high engagement with digital platforms but limited understanding of the risks involved. The methods employed in this program included field observation, educational presentations, and interactive group discussions. Through direct engagement and interactive material delivery, this initiative successfully improved participants' understanding of digital literacy, especially in terms of digital safety. The positive responses and feedback received suggest that the community is receptive to new knowledge and highlights the need for similar educational efforts in the future to ensure sustainable digital empowerment.